Development of Strength for Calcium Aluminate Cement Mortars Blended with GGBS - Hee Jun Yang; Ki Yong Ann; Min Sun Jung (Advances in Materials Science and Engineering)
In the present study, the development of strength in different calcium aluminate cement (CAC) mixture mortars with granulated ground blast-furnace slag (GGBS) was investigated. The substitution of GGBS levels was 0, 20, 40, and 60% weight of binder, of which the CAC used in this study naturally contained C2AS clinker as a secondary phase. To activate a hydraulic nature of the phase, in addition to the mineral additive, all specimens were cured at 35 ± 2°C for the first 24 hours and then stored in a 95% humidity chamber at 25 ± 2°C. The penetration resistance of fresh mortar was measured immediately after pouring, and the mortar compressive strength was monitored for 365 days. Simultaneously, to evaluate the hydration kinetics at early ages, in terms of heat evolution, the calorimetric analysis was performed at the isothermal condition (35°C) for 24 hours. The hydration behavior in the long term was characterized by X-ray diffraction, which was supported by microscopic observation using scanning electron microscopy with energy dispersive spectroscopy. Furthermore, an examination of the pore structure was accompanied to quantify the porosity. As a result, it was found that an increase in the GGBS content in the mixture resulted in an increased setting time, as well as total heat evolved for 24 hours in normalized calorimetry curves. In addition, the strength development of mortar showed a continuous increased value up to 365 days, accounting 43.8–57.5 MPa for the mixtures, due to a formation of stratlingite, which was identified at the pastes cured for 365 days using chemical and microscopic analysis. However, GGBS replacement did not affect on the pore size distribution in the cement matrix, except for total intrusion volume.